Pembatasan Kebebasan Beragama Dan Berkeyakinan Di Indonesia Serta Implikasinya: Limitation The Religion And Belief Freedom In Indonesia And Their Implications - Rohit Mahatir Manese (Reformed Center for Religion and Society, 2021)
This article aims to describe caused the restriction of religion and belief freedom and its implications in Indonesia. The author’s argument on the ownership that limitation of the religion and belief freedom in Indonesia which have mainstreams about religious values and blasphemy. It causes diversity in Indonesia to limited pluralism experience. With the perspective of pluralism, limiting the religion and belief freedom is carried out by the state makes ancestral religions which is not declared as official religions. Apart from making the state that recognizes only six religions, this statement contradicts the Universal Declaration of Human Rights (UDHR) and the International Covenant. By using the literature review method, this article finds that the religion and belief freedom in Indonesia experiences delimited pluralism so this condition brings to negotiated on ancestral religions and intolerance to minority groups. Keywords: Freedom of Religion and Belief; Religious Value; Delimited Pluralism; Discrimination; Intolerance.